Motivasi Belajar Siswa dari Keluarga Broken Home di SDN Lemahputro 1 Sidoarjo - Bahiyah, Khoridatul; Kurniawati, Rikke; Baalwi, Muhammad Assegraf; Aini, Nurul; Lestari, Wahyu Maulidya (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2024)
This research aims to determine the learning motivation of students from broken home families, determine the impact of broken home families on students, and to describe the learning motivation efforts of students at SDN Lemahputro 1 Sidoarjo. This type of research is qualitative research. This research was conducted at SDN Lemahputro 1 Sidoarjo. The data collection methods used were interviews and questionnaires. The instruments used to collect were interview guides and questionnaires that had been previously validated. Data analysis techniques use data reduction, data display, and verification. Based on the research results, it can be concluded that the information was obtained from teachers and 7 students who came from broken home families have quite low motivation to learn. The research results also explain that: Broken home has a great influence on student learning motivation. Parenting patterns in the family also influence the level of student motivation to learn. One of the things that needs to raise enthusiasm for learning is motivation. Teachers' efforts to increase the learning motivation of students from broken home families by providing additional time to study after school and approaching students by providing attention and encouragement to students to be more active in studying.